The Concept of Loving One Another Based on John 15:9-17 and Relevance For The Church Today - Fermi M. Kadek; Andreas Sudjono; Ribut Agung Sutrisno (Jurnal Teologi (JUTEOLOG), 2022)
Love is a thing that will never go stale to be discussed and discussed because love is a fundamental need for every human being. The use of the word love is very diverse, love can be used in relationships with God, husband and wife, men and women as well as relationships between parents and children. Because basically love is characterized by a relationship between two people who love each other. For this reason, in this article, researchers will explore the Lord Jesus' command regarding the concept of loving one another based on John 15:9-17. The method used is a qualitative method with a literature study approach and biblical studies presented in descriptive form. the conclusions obtained; first, we can only love if we live in the community of God's love. second, loving each other is our form of obeying God's commands, third, loving each other is shown by a self-sacrificing attitude, fourth we can love because God loves us, it is proven that He elevates us from servants to friends, fifth, we can love because we have been chosen and appointed to go bear fruit and if the fruit remains then as a form of God's love, He will give us what we ask for.